Bimbingan Teknis Tertib Administrasi Pkk Di Kelurahan Baros Kota Sukabumi - Muhammad Khairul Amal (PT. Alahyan Publisher Sukabumi, 2023)
Technical guidance on the orderly administration of the PKK is an event that aims to provide understanding and skills in running the PKK administration in an orderly and effective manner. This event was attended by PKK administrators, PKK cadres, as well as staff, and employees involved in implementing PKK programs. At this event, participants were given an understanding of regulations and regulations related to PKK, as well as tips and tricks in structuring and organizing administration, recording and documenting, archiving, as well as evaluation and monitoring. In addition, participants were also given examples of using electronic administration systems that can facilitate the management and archiving of documents. In this technical guidance, participants were invited to discuss and collaborate in finding solutions to PKK administrative problems that might be experienced in the field. Participants are expected to be able to apply the understanding and skills that have been given to the implementation of PKK programs in their respective regions. It is hoped that with technical guidance on the orderly administration of the PKK, the PKK administration can be carried out better and more effectively, so as to accelerate the achievement of the objectives of the PKK program and encourage the creation of prosperous and independent families.